Study of the Extended Phase Shift Migration for Three-Dimensional MIMO-SAR Imaging in Terahertz Band - Hang Gao; Chao Li; Shiyou Wu; Hebin Geng; Shen Zheng; Xiaodong Qu; Guangyou Fang (IEEE Access)
In this paper, the extended phase shift migration (PSM) for three-dimensional (3-D) multi-input-multi-output synthetic aperture radar (MIMO-SAR) imaging in terahertz (THz) band was studied. Based on one-dimensional MIMO arrays combined with synthetic aperture scan along another dimension, MIMO-SAR imaging scheme allows the number of array elements to be greatly reduced compared with the two-dimensional (2-D) MIMO arrays. By analyzing the derived analytical expression of the scattered waves in the frequency-wavenumber domain, the MIMO-SAR data in a certain frequency is mapped to another frequency of the ‘explode fields’ of the monostatic form in accordance with a newly defined 3-D dispersion relations. By multiplying the modified phase shift terms in each frequency of ‘explode fields’, the ‘explode fields’ at different range planes can be reconstructed. Finally, the ‘explode fields’ at time t = 0 can be successfully derived to realize fast imaging reconstruction for MIMO-SAR, with great reduction on the time consuming as compared with the BP algorithm and better accuracy compared with the Stolt migration. Additionally, due to its iterative nature in the range direction, the proposed algorithm is more flexible in treating more complicated scenarios, such as the image reconstruction in the multi-layer medium. A bistatic prototype imager was designed for the proof-of-principle experiments in THz band. The 3-D imaging results of different targets and computational complexity were also given to demonstrate the good performance of the proposed algorithm for THz MIMO-SAR imaging.